Chapter Manifesto della Public History of Education. Una proposta per connettere ricerca accademica, didattica e memoria sociale - Bandini, Gianfranco (Studi e saggi, 2019)
Public History is a great resource that belongs not only to historians, but to all those who, specialists or non-specialists, starting from their specific cultural skills, intend to adopt its dialogical style, social commitment and methodologies. In the field of educational and care professions, Public History constitutes an innovative approach, but above all a cultural commitment decidedly oriented towards social utility.